The Organization and efficiency of solid waste collection - Savas, Emanuel S. (Massachusetts : Lexington Books, 1977)
Government is big business in the United States. There are almost 80,000 governments in the country, and together they collect revenues which amount to one-third of the gross national product.' Contrary to popular impression, however, state and local governments in the aggregate are much larger than the federal government, by two important measures: (1) Most of the money spent by government for goods and services is spent by state and local governments, not the federal government; the former spent
Chapter 1. Introduction -- Chapter 2. The History of Solid Waste management -- Chapter 3. The Organization of Solid Waste Collection : A framework for Analysis -- Chapter 4. The Organization of Solid Waste Collection : Findings -- Chapter 5. Services Level for Residential Refuse Collection -- Chapter 6. Financing Solid Waste -- Chapter 7. The Cost of Residential Refuse Collection -- Chapter 8. Service Arrangement and the Cost of Residential Refuse Collection -- Chapter 9. Local Government regulation of Residential Refuse Collection -- Chapter 10. Contracts for Residential Refuse Collection -- Chapter 11. The Role of the Federal and State Governments -- Chapter 12.
Includes index.
Keywords: REFUSE COLLECTION